Translating non-efficiency goals under the Malaysian Competition Act 2010 - Abdul Rahman, Nasarudin; Ahamat, Haniff (2014)
Competition law is an important instrument to provide rules of the game for firms to compete in the market on a level playing field. It is widely accepted that the main purpose of competition law relates to economic goal, i.e. to protect the process of competition expressed in term of economic efficiency to ensure that resources are allocated in an efficient manner. It has been raised from time to time whether competition law should pursue non-efficiency objectives. More modern competition systems start to take into account the non-efficiency goals in the interpretation and implementation of their competition law. However, pursuing multiple objectives (efficiency and non-efficiency) may increase legal complexities and uncertainties, resulting in complicated tradeoffs between various objectives and exposing regulators to regulatory capture. This paper focuses on the newly enacted Malaysian competition law, namely, the Malaysian Competition Act 2010. This paper aims to study the manner in which the Malaysian competition law pursues or accommodate non-efficiency goals alongside with the economic efficiency objective as stated in the preamble of the Act. The paper highlights the role of non-efficiency goals in competition law and the issues involved in pursuing or balancing various objectives. The main thesis presented in this paper is as follows: 1) The Competition Act should not take into account non-efficiency goals unless the can be translated into efficiency gains and 2) the pursuit of non-efficiency goals such as under the name of social objective or general public interest should be accompanied with the principle of ‘proportionality’.